Evolution of the educational structure in Mexico: Document analysis of the reforms implemented during the period 2018-2024 - Castillo, Alba Marlene Chan; Torres, Arturo González; Hernández, María Luisa Pereira (Edelweiss Applied Science and Technology, 2025)
During the period 2018-2024, educational reforms in Mexico transformed the structure of the national education system with changes in policies and pedagogical approaches. The evolution of the educational structure in Mexico during this period was analyzed, identifying the factors that influenced its development and implementation. A systematic documentary analysis was carried out. The search was conducted mainly in open-access databases with specific keywords. Forty-two Spanish-language education manuscripts from Mexico from the year 2024 were analyzed using a logbook. Five main factors influenced educational evolution: the development of educational research, the implementation of new pedagogical methodologies, the formation of academic evaluation communities, the adaptation of national policies to regional contexts, and the creation of specific teaching materials. The transformation of the Mexican education system was based on documented research and systematic analysis of the changes implemented, highlighting the importance of strengthening the regional contextualization of national policies and the participation of local communities.